The Transformation of Islamic Art during the Sunni Revival - Tabbaa, Yasser, 1948- (Book collections on Project MUSE., 2001)
Ultimately, the forms and themes described in this book shaped the development of Mamluk architecture in Egypt and Syria, and by extension, the entire course of North African and Andalusian architecture as well."--Jacket.